Internalizing the Culture of Religious Tolerance in Children: Advancing the Right of Religious Freedom in Indonesia - Akbal, Muhammad; Umar, Firman; Mamonto, Moch Andry W. W. (International Journal of Criminology and Sociology, 2021)
This article aims to determine the exemplary efforts to mitigate the intolerance of Indonesia that spreads among children based on the cultural values of the Bugis Tribe, including Sipakatau, Sipakainge, and Sipakalebbi, as an effort to ensure the right to freedom guaranteed in the 1945 Constitution and the International Covenant on Civil and Political Rights. This type of legal-normative research is descriptive-prescriptive, focusing on examining primary legal materials and legal materials, using statutory, conceptual, and historical approaches. The results of the study show that the cultural values of Sipakatau, Sipakainge, and Sipakalebbi, which are the value system or way of life of the Bugis tribe, contain the meaning of religious tolerance, namely Sipakatau implies mutual respect for God’s creation; Sipakinge, reminding each other not to do things in the form of disrespect for people of different religions; and Sipakalebbi with the meaning of loving fellow-creatures regardless of religion. Based on its authority, the Indonesian government should formulate policies to internalize tolerance based on the cultural values of Sipakatau, Sipakainge, and Sipakalebbi. This can be done by referring to the findings as a sociological formulation of regional regulations regarding early childhood education curriculum.